2009
DOI: 10.1007/s10529-009-0061-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing immune responses against SARS-CoV nucleocapsid DNA vaccine by co-inoculating interleukin-2 expressing vector in mice

Abstract: The immunogenicity of SARS-CoV nucleocapsid DNA vaccine and the immunoregulatory activity of interleukin-2 (IL-2) were investigated. DNA vaccine plasmids, pcDNA-N and pcDNA-IL2, were constructed and inoculated into BALB/c mice with or without pcDNA-IL2 by intramuscular injection. Cellular and humoral immune responses were assessed by indirect ELISA, lymphocyte proliferation assays, ELISPOT and FACS. The nucleocapsid DNA vaccine had good immunogenicity and can induce specific humoral and cellular immunity in BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The N protein of human CoV is abundantly produced during infection and exhibits strong immunogenicity and conservancy, which can act as an ideal immunogen to elicit both cellular and humoral immune responses [50]. It is noteworthy that a large number of previous studies have shown the feasibility of the N protein as an immune target antigen or vaccine product [51][52][53][54][55][56][57][58][59][60]. Ma et al demonstrated that a SARS-CoV vaccine based on the N gene that was expressed by DNA plasmid and adenovirus vector could induce detectable antibody and IFN-γ [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N protein of human CoV is abundantly produced during infection and exhibits strong immunogenicity and conservancy, which can act as an ideal immunogen to elicit both cellular and humoral immune responses [50]. It is noteworthy that a large number of previous studies have shown the feasibility of the N protein as an immune target antigen or vaccine product [51][52][53][54][55][56][57][58][59][60]. Ma et al demonstrated that a SARS-CoV vaccine based on the N gene that was expressed by DNA plasmid and adenovirus vector could induce detectable antibody and IFN-γ [51].…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al demonstrated that a SARS-CoV vaccine based on the N gene that was expressed by DNA plasmid and adenovirus vector could induce detectable antibody and IFN-γ [51]. Similar studies of the DNA vaccine based on the SARS-CoV N gene have shown potential inducing specific humoral and cellular immunity in BALB/c mice [52,53]. Moreover, multiple immunodominant B-cell epitopes, helper T-cell epitopes and CTL epitopes were mapped on the N protein of SARS-CoV [54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…vaccines, increased immune responses to hepatitis C core antigen [82], glycoprotein E2 of bovine diarrheal virus [83], and the S glycoprotein and nucleocapsid of SARS-coronavirus (SARS-CoV) [83,84]. Co-expression of IL-2 with genes encoding influenza A (H1N1 subtype) HA and neuraminidase in a bicistronic plasmid was more effective than coexpression of IL-12 or GM-CSF in protecting mice from lethal influenza infection [85].…”
Section: Il-2 Stimulates the Proliferation Of Both T And Nk Cells Andmentioning
confidence: 99%
“…Cytokine-encoding plasmids can be prepared along with the antigen-expressing plasmid and, local expression of cytokines at the injection site avoids the potential toxicity of systemically administered cytokines. Interleukin (IL)-2 induces the proliferation of T and NK cells, and has been extensively studied as a genetic adjuvant [73][74][75][76][77][78][79][80][81][82]. A fusion construct of Mycoplasma pneumoniae p1 gene carboxy terminal region with IL-2 resulted in enhanced vaccine responses in mice [83].…”
Section: Plasmid-encoded Cytokinesmentioning
confidence: 99%